2018
DOI: 10.1186/s12877-018-0729-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between residual teeth number in later life and incidence of dementia: A systematic review and meta-analysis

Abstract: BackgroundIt has been suggested that tooth loss in later life might increase dementia incidence. The objective of this analysis is to systematically review the current evidence on the relationship between the number of remaining teeth and dementia occurrence in later life.MethodsA search of multiple databases of scientific literature was conducted with relevant parameters for articles published up to March 25th, 2017. Multiple cohort studies that reported the incidence of dementia and residual teeth in later l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 56 publications
0
56
1
1
Order By: Relevance
“…It has been hypothesized that certain oral diseases could have an influence on AD either by causing a low‐grade inflammation, by activating microglia cells via proinflammatory molecules, or by microbial invasion into the brain . It has also been speculated that the effects of oral diseases on cognitive function might be mediated through changes in diet that in turn are related to impaired mastication …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It has been hypothesized that certain oral diseases could have an influence on AD either by causing a low‐grade inflammation, by activating microglia cells via proinflammatory molecules, or by microbial invasion into the brain . It has also been speculated that the effects of oral diseases on cognitive function might be mediated through changes in diet that in turn are related to impaired mastication …”
Section: Discussionmentioning
confidence: 90%
“…[8][9][10]22,23 It has also been speculated that the effects of oral diseases on cognitive function might be mediated through changes in diet that in turn are related to impaired mastication. 24,25 It must be emphasized that this study has a cross-sectional design and that we cannot draw any conclusions about the causal role of oral diseases in the development and progression of AD because we do not have data about the initiation and progression of AD, or other dementias, or oral diseases. This prevents us from determining whether oral diseases are a cause or a consequence of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies have suggested associations between cognitive ability and oral conditions, such as number of teeth (Luo et al, 2015;Li et al, 2017;Oh et al, 2018) and dental occlusion (Ono et al, 2010;Franco et al, 2012;Takeuchi et al, 2015). Furthermore, occlusal force (Takeshita et al, 2016;Ikebe et al, 2018) and chewing ability have been shown to have effects on cognitive ability (Chen et al, 2015;Natalie et al, 2015;Seraj et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have attempted to summarize the evidence that correlates oral health conditions with dementia [2][3][4][5]. The importance of adequate mental health on the drive and ability to care for oneself is somewhat intuitive.…”
mentioning
confidence: 99%
“…Recent systematic reviews showed somewhat contradictory conclusions regarding the connection between tooth loss and dementia. They ranged from identifying positive association [2,3], in which tooth loss resulted in approximately 20% to 50% increase in the risk of developing dementia, to suggesting no association at all [5]. Although most current literature positively associates tooth loss with dementia, the quality of this evidence is arguable [3,4].…”
mentioning
confidence: 99%